2016
DOI: 10.3390/nu8070407
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Vector Analysis and Muscular Fitness in Healthy Men

Abstract: Muscle strength can define the general muscular fitness (MF) measurable through hand-grip strength (HG), which is a factor that relates to the health of people of different ages. In this study we evaluated the muscle strength together with a bioimpedance electric analysis in 223 healthy Colombian adult subjects. The bioelectrical impedance vector analysis (BIVA) was conducted to determine the resistance (R), reactance (Xc) and phase angle (PhA). We classified the subjects into three groups (for tertiles), obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 37 publications
7
34
0
6
Order By: Relevance
“…A study of in inpatient subjects showed a different trend for the vector shift; the average vector displaced with increasing HSG due to decreased R/H, but increased Xc/H [25]. Interestingly, our study showed an increase in PhA with increasing HSG in healthy adults using whole body, right limb, and left limb modes, which is consistent with previous studies of healthy young adult [29] and inpatient subjects [25]. Moreover, PhA has been validated as a good predictor of nutritional and functional status [45][46][47].…”
Section: Compared To Body Composition Analysis Vector Analysis Uses supporting
confidence: 90%
See 2 more Smart Citations
“…A study of in inpatient subjects showed a different trend for the vector shift; the average vector displaced with increasing HSG due to decreased R/H, but increased Xc/H [25]. Interestingly, our study showed an increase in PhA with increasing HSG in healthy adults using whole body, right limb, and left limb modes, which is consistent with previous studies of healthy young adult [29] and inpatient subjects [25]. Moreover, PhA has been validated as a good predictor of nutritional and functional status [45][46][47].…”
Section: Compared To Body Composition Analysis Vector Analysis Uses supporting
confidence: 90%
“…Volume-adjusted R and Xc have also been used to construct specific BIVA plots In this study, a significant migration of the mean vectors with increasing HGS was observed due to decreased Xc/H and R/H in the healthy adults in this study. A similar finding was reported in a study of healthy young adults by Rodriguez-Rodriguez et al [29]. A study of in inpatient subjects showed a different trend for the vector shift; the average vector displaced with increasing HSG due to decreased R/H, but increased Xc/H [25].…”
Section: Compared To Body Composition Analysis Vector Analysis Uses supporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the positions of impedance vectors in paretic regions were below than those in non-paretic regions in severe and mild hemiplegic stroke subjects. A similar phenomena that Xc/H in paretic regions of severe stroke patients was significantly reduced was reported in BIVA diagram aimed at the elderly with malnutrition and impaired functionality [31,32]. Evaluation of functional statue in hemiplegic stroke subjects after stroke has been mainly performed in indirect method through the rehabilitation assessment tools such as hand grip strength [33], manual function test (MFT) developed by Sakai [34], and activities of daily living (ADL) using the modified Barthal index (MBI) [35].…”
Section: Bioelectrical Impedance Parameterssupporting
confidence: 77%
“…However, in the area of discussed correlations, not only muscle mass is important, but also muscle quality, with consideration of such parameters as: composition, metabolism, aerobic capacity, insulin resistance, fat infiltration, fibrosis, etc. It should also be remembered that the loss of muscle mass does not fully explain the loss of function [28]. Positive correlations between FFM, SMM, as well as BMI and the PhA values, result from the fact that PhA increases together with an increase in the number of cellular membranes, exerting an effect on the magnitude of the reactance.…”
Section: Discussionmentioning
confidence: 99%